Dampak Pelayanan Sistem Check in 24 Jam dalam Meningkatkan Loyalitas Tamu di Janevalla Bandung - Vania, Moch Firman Dwi; Farisya, Ghaida; Firman, Deden (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
The growing competition in the hospitality industry has prompted hotels to innovate their service systems; one of which is the implementation of a 24-hour check-in policy. This study examines the impact of such a service system on guest loyalty at janevalla hotel bandung. A descriptive qualitative approach was employed; with data gathered through semi-structured in-depth interviews; non-participant observation; and document analysis. Informants were selected purposively and consisted of the duty manager; a front office staff member; and one loyal guest. Data analysis followed the interactive model of miles; huberman; and saldaña; with credibility ensured through source triangulation and member checking. The findings indicate that the 24-hour check-in system provides time flexibility perceived by guests as added value compared to conventional hotels. Guest loyalty emerged through a combination of service flexibility; quality of staff interaction, and positive overall stay experience; manifested in repeat visit behavior and willingness to recommend the hotel to others. Viewed through the servqual framework; the service practices reflect dimensions of responsiveness, empathy; and assurance. This study affirms that customer-centered service innovation contributes meaningfully to strengthening guest loyalty within the context of urban lifestyle hotels in indonesia.